Quantitative evaluation of wireless ultra wideband loss due to transmission gain and group delay - Chantarawat, Chartchai; Promwong, Sathaporn (My University, 2011)
In this paper, we evaluated the effect of transmission gain and group delay in ultra wideband transmission by using the Friis' transmission formula. However, it is not directly applicable to ultra wideband impulse radio (UWB-IR) transmission systems. This paper presents the evaluation formula in the term of transmission gain and group delay for the UWB-IR that takes into account the transmitted waveform, its distortion due to the antennas, the channel and the correlation receiver. Since the antennas are significant pulse-shaping filters in UWB impulse radio, the various kinds of the antennas are experimentally examined, especially focused on the effect of the received signal. © 2011 IEEE.
Keywords: Friis' transmission formula; group delay; impulse radio; UWB transmission; UWB-IR